2019
DOI: 10.1167/tvst.8.6.36
|View full text |Cite
|
Sign up to set email alerts
|

Topical Brimonidine or Intravitreal BDNF, CNTF, or bFGF Protect Cones Against Phototoxicity

Abstract: Purpose: To develop a focal photoreceptor degeneration model by blue lightemitting diode (LED)-induced phototoxicity (LIP) and investigate the protective effects of topical brimonidine (BMD) or intravitreal brain-derived neurotrophic factor (BDNF), ciliary neurotrophic factor (CNTF), or basic fibroblast growth factor (bFGF). Methods: In anesthetized, dark-adapted, adult female Swiss mice, the left eye was dilated and exposed to blue light (10 seconds, 200 lux). After LIP, full-field electroretinograms (ERG) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(75 citation statements)
references
References 95 publications
(143 reference statements)
5
70
0
Order By: Relevance
“…19,57 In this study, we show that 1 month ALE, there are high numbers of activated microglial cells and/or macrophages in the photoreceptor layers at the center and periphery of the rings of cone degeneration, suggesting that these cells may be involved in the phagocytosis of the dead photoreceptors. Other authors have also found migration of microglia and macrophages to the outer retina in other models of light-induced retinal degeneration 59,110 and activated microglial cells at the center of the rings of photoreceptor degeneration in a rat model of inherited retinal degeneration, before the occupation of the rings by processes of Müller cells. 29 Microglial cells and Müller cells might act coordinately to phagocytose photoreceptor debris during retinal degeneration 48,49,60,111,112 ; Müller cells may release factors that induce microglial activation and migration, 96,100,103 and may also form a scaffold to guide microglial migration, 49,60 whereas activated microglia may also release factors that influence Müller cells behavior.…”
Section: Figurementioning
confidence: 79%
See 1 more Smart Citation
“…19,57 In this study, we show that 1 month ALE, there are high numbers of activated microglial cells and/or macrophages in the photoreceptor layers at the center and periphery of the rings of cone degeneration, suggesting that these cells may be involved in the phagocytosis of the dead photoreceptors. Other authors have also found migration of microglia and macrophages to the outer retina in other models of light-induced retinal degeneration 59,110 and activated microglial cells at the center of the rings of photoreceptor degeneration in a rat model of inherited retinal degeneration, before the occupation of the rings by processes of Müller cells. 29 Microglial cells and Müller cells might act coordinately to phagocytose photoreceptor debris during retinal degeneration 48,49,60,111,112 ; Müller cells may release factors that induce microglial activation and migration, 96,100,103 and may also form a scaffold to guide microglial migration, 49,60 whereas activated microglia may also release factors that influence Müller cells behavior.…”
Section: Figurementioning
confidence: 79%
“…19,34,[50][51][52] In any case, previous works have shown that microglial cells become activated and travel through the retina in animal models of retinal degeneration, 34,35,50,[52][53][54][55][56][57][58] and are also present in the center of the rings of rod-cone degeneration. 29,59 There is also evidence that there is an interaction between microglial and Müller cells that affects trophic factor release by Müller cells 60 and therefore this interplay may also be important to regulate the responses of Müller cells in different scenarios, such as the regenerating zebrafish retina, 61 in animal models of retinal degenerations 62 and also in cocultures of activated microglia and Müller cells. 60 In this study, we have used our previously described model of light-induced retinal degeneration 2,3,13,15 and immunodetection of cones, Müller and microglial cells to investigate the role of the macro-and microglial cells in the rings of photoreceptor degeneration.…”
mentioning
confidence: 99%
“…Therefore, taking into account this risk factor, many animal models of light-induced retinal degeneration have been developed, and serve to study the evolution of the degeneration and to test possible protective strategies [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Several of these studies have documented the effect of excessive exposure to short-wave visible light (blue light) on the retina [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Blue light, the most damaging component of sunlight, causes oxidative stress that induces the loss of retinal pigment epithelium cells and photoreceptors [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several of these studies have documented the effect of excessive exposure to short-wave visible light (blue light) on the retina [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Blue light, the most damaging component of sunlight, causes oxidative stress that induces the loss of retinal pigment epithelium cells and photoreceptors [ 13 , 14 , 15 , 16 , 17 , 18 ]. We have recently characterized a new focal blue light emitting diode (LED) induced phototoxicity (LIP) model in albino mice that results in focal phototoxic cone degeneration in an area of the retina that coincides with the highest density of rodent photoreceptors [ 16 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation